Karyotypic diversification and its contribution to the taxonomy of Eleocharis (Cyperaceae) from Brazil - Maximiano da Silva, Carlos Roberto [UNESP]; Trevisan, Rafael; Socorro Gonzalez-Elizondo, Maria; Ferreira, Josue Maldonado; Laforga Vanzela, Andre Luis (CSIRO Publishing, 2010)
A karyotype analysis of 147 populations of 25 Brazilian species of Eleocharis (Cyperaceae) was carried out, including representatives of the three subgenera that occur in the country: Limnochloa, Scirpidium and Eleocharis. The analyses showed chromosomes without centromeres, but with terminal nucleolar constrictions (satellites) in some chromosomes. The chromosome numbers varied from 2n = 6 in E. subarticulata and E. maculosa to 2n = 60 in E. laeviglumis, but the chromosome basic number x = 5 was confirmed. Species of the subgenera Eleocharis and Scirpidium possess fewer and larger chromosomes, while those in the subgenus Limnochloa have small and more numerous chromosomes. These features indicate that the karyotypes of the subgenera Eleocharis and Scirpidium are more closely related, in agreement with morphological and phylogenetical data. The representatives of the section Eleocharis exhibited the largest differences in chromosome number and size, probably due to chromosome fission and fusion. Polyploidy was the most common event in this group. Nevertheless, most of the studied species exhibited regular meiosis with only bivalent formation, even the polyploids, such as in E. geniculata and E. sellowiana. The cytogenetic information obtained showed quite variable karyotypes with chromosomes gradually decreasing in size, and predominance of polyploidy. These results are useful in the differentiation of the subgenera.